Infertility Related Psychological Distress and Group Based Compassion Focused Therapy: A Conceptual Analysis in Collectivist Contexts - Tayyeba Ahmad; Dr. Naheed Atta; Dr. Muhammad Luqman Khan (ACADEMIA International Journal for Social Sciences, 2025)
Infertility is a major global public health concern with significant psychological, relational, and sociocultural consequences, particularly for women living in collectivist societies. Beyond its biomedical aspects, infertility often threatens personal identity, marital stability, and social acceptance. In cultures such as Pakistan, where motherhood is closely linked to feminine identity and family expectations, infertility can lead to intense psychological distress characterized by depression, anxiety, shame, and internalized stigma. Understanding these psychological dimensions is essential for developing culturally sensitive therapeutic interventions. The primary objective of this traditional literature review was to synthesize empirical research on infertility-related psychological distress and to examine the potential effectiveness of Compassion-Focused Therapy (CFT), particularly in group-based formats, for reducing shame, self-criticism, and emotional distress among women in collectivist contexts. Additionally, the review aimed to identify research gaps and highlight the need for culturally adapted psychological interventions in South Asian societies.  A PRISMA-guided screening process was used to identify relevant studies examining infertility-related psychological distress and compassion-based therapeutic interventions. After removing duplicates and applying inclusion criteria, a total of 60 studies were included in the final review. The selected literature comprised diverse research designs, including quantitative cross-sectional studies (n =24), randomized controlled trials (n =12), quasi-experimental studies (n =8), qualitative studies (n =10), and mixed-method studies (n =6). Studies were evaluated based on methodological rigor, clarity of outcome measures, and relevance to infertility-related psychological experiences and compassion-based interventions.  The findings consistently indicate that infertility is associated with high levels of psychological distress, particularly depression, anxiety, chronic stress, and emotional dysregulation. Shame and self-criticism emerged as central emotional mechanisms underlying infertility-related suffering. Evidence suggests that Compassion-Focused Therapy is effective in reducing shame, self-criticism, and emotional distress by strengthening the soothing emotional regulation system and cultivating self-compassion. Group-based CFT interventions further promote normalization, shared experiences, and social support, which may be particularly beneficial in collectivist cultural contexts. Overall, the review highlights the potential of culturally adapted, group-based CFT as a promising intervention for addressing infertility-related psychological distress. Future research should prioritize randomized controlled trials in South Asian populations to validate and culturally adapt compassion-based therapeutic approaches.